Immune reconstitution following alemtuzumab therapy is characterized by exhausted T cells, increased regulatory control of proinflammatory T cells and reduced B cell control - von Essen, Marina Rode; Chow, Helene Højsgaard; Holm Hansen, Rikke; Buhelt, Sophie; Sellebjerg, Finn (Frontiers in Immunology, 2023)
Alemtuzumab is a monoclonal antibody targeting CD52 on the surface of immune cells, approved for the treatment of active relapsing-remitting multiple sclerosis (RRMS). The purpose of this study was to analyze the repopulation of peripheral lymphocytes following alemtuzumab-induced lymphocyte depletion and investigate associations with disease activity and development of secondary autoimmunity. For this, blood samples were collected two years after initiation of alemtuzumab treatment and lymphocytes were subjected to a comprehensive flow cytometry analysis. Included in the study were 40 patients treated with alemtuzumab and 40 treatment-naïve patients with RRMS. Disease activity and development of secondary autoimmune disease was evaluated after three years of treatment. Our study confirms that alemtuzumab treatment profoundly alters the circulating lymphocyte phenotype and describes a reconstituted immune system characterized by T cell activation/exhaustion, an increased regulatory control of IL-17 producing effector T cells and CD20 + T cells, and a reduced control of B cells. There were no obvious associations between immune cell subsets and disease activity or development of secondary autoimmune disease during treatment with alemtuzumab. Our results indicate that the reconstituted immune response is skewed towards a more effective regulatory control of MS-associated proinflammatory T cell responses. Also, the enlarged pool of naïve B cells together with the apparent decrease in control of B cell activity may explain why alemtuzumab-treated patients retain the ability to mount a humoral immune response towards new antigens.